Follow-up dental examination a day after apicoectomy using the store-and-forward method - Miladinović, Milan; Živković, Dušan; Živković, Milan; Lazić, Zoran; Karanović, Andrijana; Mihailović, Djordje; Šehalić, Meliha; Duka, Miloš (Vojnosanitetski pregled, 2021)
Background/Aim. Although apicoectomy is performed routinely and yields excellent results, a close patient observation during the postoperative course is desirable in order to avoid possible complications. The aim of this study was to investigate the adequacy of postoperative control visits a day after surgery using the store-and-forward telemedicine method compared to the clinical in-person controls. Methods. A total of 122 apicoectomies were performed during 115 dental surgery interventions. The follow-up dental examination a day after apicoectomy consisted of reviewing extraoral and intraoral photographs on the internet and reviewing responses to the questionnaire. After that, patients were examined in-person. Cohen’s kappa („store-and-forward” method) coefficient, diagnostic sensitivity (SE), sensitivity (SP), and efficiency (EFF) were determined. Statistical comparisons were performed using the Z-test, and nonparametric characteristics were tested using McNemar’s χ2-test at the statistical significance cut-off value of p = 0.05. Results. There were 106 (92%) patients seen at the control dental examination. The agreement between in-person and store-and-forward telemedicine method was found in 104 (98%) cases. The obtained agreement values (K = 0.85, S = 0.99, SP = 0.86, EFF = 0.98) indicated an almost complete diagnostic agreement. Conclusion. Based on the internet transmission of patients’ digital photographs and accompanying patient medical history records, the study showed that the in-person control dental examinations a day after surgery can be successfully replaced with the remote store-and-forward method of telemedicine.
Keywords: apicoectomy; dental root; dentistry; oral surgical procedures; sensitivity and specificity; telemedicine